Complete mitochondrial genome of the acrobat ant Crematogaster teranishii Santschi, 1930 (Formicidae; Hymenoptera). Issue 2 (1st February 2021) - Park, Jonghyun; Xi, Hong; Park, Jongsun
Abstract: The genus Crematogaster is a diverse group of ants found around the world. We have completed the mitochondrial genome of Crematogaster teranishii, which is the first mitochondrial genome of the genus. The mitochondrial genome is 17, 442 bp long and 20.3% in GC ratio, which is similar to those of other ants. It contains 13 protein-coding genes, two ribosomal RNAs, 22 transfer RNAs, and a control region with same gene order to other myrmicine species. The intergenic region between nad3 and trnA was unusually long compared to other ant species. Phylogenetic analysis showed that C. teranishii was closely related to other members of tribe Crematogastrini.